Design of a moderate‐wideband superconducting filter with modified stub structure. Issue 4 (8th December 2017) - Lu, Xinxiang; Guo, Xubo; Heng, Yong; Luo, Chenjie; Wei, Bin; Zhang, Liuwan; Cao, Bisong
Abstract: This paper presents a design method for moderate‐wideband filters with modified λ/2 stub resonators mid‐tapped by λ/4 connecting lines which act as admittance inverters. The modified tapped‐stubs avoid low characteristic impedances of the stubs which results in a very wide strip‐width and a large circuit size. An example filter at 2250 MHz with a fractional bandwidth (FBW) of 45% is successfully designed with this method and fabricated. It has a compact size of 26.5 mm × 10.5 mm on a YBCO/LaAlO3 superconducting wafer. The measurements show good response and match well with the simulations.